2021
DOI: 10.1093/rheumatology/keab781
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology, salivary flow and ultrasonography of the parotid gland: three complementary measurements in primary Sjögren’s syndrome

Abstract: Objective The involvement of salivary glands in primary Sjögren’s syndrome (pSS) can be assessed in different ways: histopathology, salivary flow and ultrasonography. To understand the relative value of these different approaches, it is crucial to understand the relationship between them. As we routinely perform these three modalities in the parotid gland for disease evaluation, our aim was to investigate the construct validity between these modalities in one and the same gland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…However, they also showed that a FS ≥1 is not always reflected by the presence of hypoechogenic areas in the parotid gland, and the presence of hypoechogenic areas is not always reflected by a positive FS, indicating that parotid gland histopathology and parotid gland ultrasonography assess only partly related constructs in pSS. (42). Similar correlations between FS and ultrasound scores were found in a study comparing labial gland ultrasound with histopathology of the labial gland (43).…”
Section: Salivary Gland Biopsysupporting
confidence: 70%
“…However, they also showed that a FS ≥1 is not always reflected by the presence of hypoechogenic areas in the parotid gland, and the presence of hypoechogenic areas is not always reflected by a positive FS, indicating that parotid gland histopathology and parotid gland ultrasonography assess only partly related constructs in pSS. (42). Similar correlations between FS and ultrasound scores were found in a study comparing labial gland ultrasound with histopathology of the labial gland (43).…”
Section: Salivary Gland Biopsysupporting
confidence: 70%
“…Thus, the presence of LELs is indicative of more severe serological abnormalities and glandular disease and could be employed to identify pSS patients with pronounced (pathogenic) B cell involvement. Patients with LELs also demonstrate significantly higher presence of hypoechoic regions of the parotid SG as identified by ultrasound (10). Considering the size of LELs however (in the µm range), compared to the very large, macroscopic nature of hypoechoic regions, LELs are unlikely to be the sole source of hypoechoic regions in the SG in pSS.…”
Section: Relation Between Lels and Clinical And Immunological Featuresmentioning
confidence: 89%
“…The relationship between LGUS features and LG pathology, and indeed tear production still needs to be further explored. We have recently shown in the salivary gland of pSS patients that ultrasound, histology and function are 3 independent measures, depicting apparently distinct pathological events in pSS (5). If this also applies to the LG with relation to Schirmer's tests or the OSS test remains to be investigated, as indeed does that between SGUS and LGUS of the same patient.…”
Section: Conclusion and Further Researchmentioning
confidence: 97%
“…The pathology of the salivary gland in Sjögren's syndrome The volume of both 'whole mouth' saliva, that is the combination of saliva produced by all SGs working in concert, and that of saliva specific to particular salivary glands, is decreased in pSS patients, compared to sicca controls (1)(2)(3)(4). Lymphocytic infiltration invades the SGs, but the extent of this infiltration appears poorly correlated with the degree of salivary gland function (5,6). Lymphocytic infiltration invades the major and minor SGs in pSS patients congregating in 'foci' around the SG striated ducts.…”
Section: The Salivary Gland In Pssmentioning
confidence: 99%
See 1 more Smart Citation